Hydrogen Embrittlement of Ferritic-Perlitic and Martenzitic Pipe Steels - Knaislová, Anna; Zmeko, Jan; Reiser, Matěj; Macháčková, Nikola; Vojtěch, Dalibor (Manufacturing Technology Journal, 2025)
This study investigates the susceptibility of two pipeline steels, ferritic-pearlitic CSN 12022 and martensitic L80, to hydrogen embrittlement. Electrolytic hydrogen charging increased the absorbed hydrogen content approximately fivefold in both steels, with the martensitic grade showing higher uptake due to its dense dislocation network and carbide distribution. Tensile tests demonstrated that hydrogen had little influence on yield or ultimate tensile strength but caused a severe reduction in ductility. Elongation dropped from 39 % to 13 % in CSN 12022 and from 25 % to 11 % in L80. Fractographic analysis confirmed a transition from ductile dimple fracture to quasi-cleavage fracture in the hydrogen-charged condition. These findings confirm that microstructure strongly affects hydrogen embrittlement: ferritic-pearlitic steel undergoes a more dramatic relative loss in ductility, while martensitic steel retains higher strength but exhibits significant hydrogen-assisted cracking. The results highlight the importance of considering hydrogen effects in the design and application of steels for energy and gas transport systems.
Keywords: Hydrogen embrittlement; Mechanical properties; Tensile tests; CSN 12022 steel; L80 steel